Automated identification of exudates and optic disc based on inverse surface thresholding - Haniza, Yazid; Hamzah, Arof, Dr.; Hazlita, Mohd Isa, Dr. (Springer Science+Business Media, LLC., 2012)
Link to publlisher's homepage at http://www.springerlink.com/